Bridging Policy and Practice: A Systematic Literature Review on Dual-Approach Educational Innovation - Disa Sri Ilma Aditya; Andri Ani Suryawijaya; Riska Meisyi Putri; Muhammad Ali Basroh; Retno Wahyu Ningsih (Universitas Nurul Jadid Probolinggo, Indonesia, 2025)
Educational innovation has become a crucial strategy for improving learning quality and strengthening schools’ capacity to respond to rapid technological and societal changes. This study aims to analyze the implementation strategies of educational innovation through top-down and bottom-up approaches, identify the factors influencing their effectiveness, and propose an integrated implementation model based on recent empirical evidence. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Relevant articles published between 2022 and 2026 were systematically retrieved from Google Scholar, Scopus, ERIC, ScienceDirect, and SpringerLink using predefined search terms related to educational innovation and implementation strategies. The findings reveal that the top-down approach provides strategic policy direction, standardized implementation, and institutional resource support, whereas the bottom-up approach promotes teacher participation, contextual problem-solving, and innovation driven by local needs. Leadership, teacher competence, organizational culture, and technological infrastructure were identified as the primary enabling factors, while resistance to change and limited resources remained the most significant challenges. The study implies that integrating top-down and bottom-up approaches can establish a balanced, adaptive, and sustainable framework for implementing educational innovation and enhancing school effectiveness across diverse educational contexts.